Branding the Kingdom of Saudi Arabia / Ibrahim Alsedrah - Alsedrah, Ibrahim (Research Management Centre (RMC), 2021)
Country branding is a systematic process of organising the country's actions, behaviour, investments, innovations, and communications to achieve a desirable reputation. On the other hand, the country image represents the stereotyping of a country that does not always represent its identity, and that is the case of the Kingdom of Saudi Arabia (KSA). Despite KSA's achievements, especially after the 2030 ambitious vision, it is mostly perceived as an oil-producing country. Therefore, this study aims to: review the concept of country image, identity, and branding examples, as well as evaluate the KSA current brand based on secondary information. The author uses a relevant literature review to explore the topic. This paper finds (1) a lack of a strategic plan, studies, and suggest the establishment of branding authority in KSA. (2) Branding KSA is highly essential for two reasons: First, Branding will help KSA to highlight the 2030 vision successes and extend its image beyond the traditional perception. Second, branding is significant, especially with the current competition between countries. The paper may be first to bring attention to the importance of country branding in the KSA context.